Exhaustion of nucleus pulposus progenitor cells with ageing and degeneration of the intervertebral disc - Sakai, Daisuke (Nature Pub. Group, 2012)
Despite the high prevalence of intervertebral disc disease, little is known about changes in intervertebral disc cells and their regenerative potential with ageing and intervertebral disc degeneration. Here we identify populations of progenitor cells that are Tie2 positive (Tie2(+)) and disialoganglioside 2 positive (GD2(+)), in the nucleus pulposus from mice and humans. These cells form spheroid colonies that express type II collagen and aggrecan. They are clonally multipotent and differentiated into mesenchymal lineages and induced reorganization of nucleus pulposus tissue when transplanted into non-obese diabetic/severe combined immunodeficient mice. The frequency of Tie2(+) cells in tissues from patients decreases markedly with age and degeneration of the intervertebral disc, suggesting exhaustion of their capacity for regeneration. However, progenitor cells (Tie2(+)GD2(+)) can be induced from their precursor cells (Tie2(+)GD2(−)) under simple culture conditions. Moreover, angiopoietin-1, a ligand of Tie2, is crucial for the survival of nucleus pulposus cells. Our results offer insights for regenerative therapy and a new diagnostic standard.